2022
DOI: 10.2166/wcc.2022.356
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of innovative trend approaches (ITA with significance test and IPTA) comparing to the classical trend method of monthly and annual hydrometeorological variables: a case study of Ankara region, Turkey

Abstract: The difficulty of monitoring hydrometeorological trends remains relevant because of the importance of climate change. In this study, innovative polygon trend analysis (IPTA), new graphical methods, have recently been presented, Mann-Kendall and innovative trend analysis (ITA) with significance tests are employed at monthly and annual hydrometeorological data for Ankara province in Turkey. Finally, sequential Mann-Kendall (SQ-MK), CUSUM, and standard normal homogeneity test (SNHT) are applied to detect any abru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Moreover, the ITA method complies perfectly with the other applied methods but with higher percentages than the others. This discrepancy can be explained by the ability of this method to unmask hidden increasing (decreasing) trends in the time series in Turkey (Esit, 2022; Güçlü, 2020), in Southern Italy (Caloiero, 2019) and in China (Dong et al, 2020; Li et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ITA method complies perfectly with the other applied methods but with higher percentages than the others. This discrepancy can be explained by the ability of this method to unmask hidden increasing (decreasing) trends in the time series in Turkey (Esit, 2022; Güçlü, 2020), in Southern Italy (Caloiero, 2019) and in China (Dong et al, 2020; Li et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The examination of trends in meteorological variables is a vital topic of research before the projection of future climate variables since climate change continues to have an impact on many facets of life (Birpnar et al, 2023;Sen et al, 2019;Esit, 2023). The identification of climate change impact in a specific area often relies on the analysis of key meteorological variables such as precipitation and air temperature (Dong et al, 2020).…”
Section: Trend Analysismentioning
confidence: 99%
“…Moreover, this method is capable of uncovering monthly and seasonal variations that may not be detected by the traditional annual hydrometeorological analysis (Sen et al, 2019). Several studies currently apply the IPTA technique and suggest its capacity for exploring the hidden trends that occur during the holistic annual trend detection approach (Akcay et al, 2022;Esit, 2023;Sen et al, 2019). Akcay et al (2022) applied both IPTA and Man Kendall (MK) for trend analysis of winds and waves and indicated that the IPTA method is more sensitive and detects more trends than the MK method.…”
Section: Innovative Polygon Trend Analysis (Ipta)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, as the existing data can be divided into any number of clusters, unlike rank‐based statistical tests, a monotonous trend is not the only type that can be detected. This feature allows the method to offer a more flexible approach, and therefore, it has been used in various studies and compared with classical approaches (Dabanlı et al, 2016; Esit, 2023; Gumus et al, 2023; Phuong et al, 2020; Touhedi et al, 2023). Güçlü (2020) suggested the improved visualization of the ITA (IV‐ITA) approach to determine trend conditions.…”
Section: Introductionmentioning
confidence: 99%